Magnetic Molecularly Imprinted Chitosan Combined with a Paper-Based Analytical Device for the Smartphone Discrimination of Tryptophan Enantiomers - Abdelhafid Karrat; Juan José García-Guzmán; José María Palacios-Santander; Aziz Amine; Laura Cubillana-Aguilera (Biosensors, 2023)
The separation of enantiomers plays a critical role in pharmaceutical development, ensuring therapeutic efficacy, safety, and patent protection. It enables the production of enantiopure drugs and enhances our understanding of the properties of chiral compounds. In this study, a straightforward and effective chiral detection strategy was developed for distinguishing between tryptophan (TRP) enantiomers. The approach involved the preparation of a magnetic molecularly imprinted chitosan (MMIC) for preparation of the sample, which was combined with a nitrocellulose membrane (a paper-based analytical device, PAD) integrated with D-TRP covalently grafted with polymethacrylic acid (PAD-PMA_D-TRP). Discriminating between the TRP enantiomers was achieved using AuNPs as a colorimetric probe. Indeed, the presence of D-TRP rapidly induced the aggregation of AuNPs due to its strong affinity to PAD-PMA_D-TRP, resulting in a noticeable change in the color of the AuNPs from red to purple. On the other hand, L-TRP did not induce any color changes. The chiral analysis could be easily performed with the naked eye and/or a smartphone. The developed method exhibited a detection limit of 3.3 µM, and it was successfully applied to detect TRP in serum samples, demonstrating good recovery rates. The proposed procedure is characterized by its simplicity, cost-effectiveness, rapidity, and ease of operation.